2007
DOI: 10.1111/j.1365-2613.2006.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

c‐Myc partially mediates IFNγ‐induced apoptosis in the primary hepatocyte

Abstract: Interferon-gamma (IFNgamma) is a central component of the complex cytokine and inflammatory response that contributes to liver cell injury in hepatitis. We report that in the primary hepatocyte IFNgamma synergizes with the mechanistically distinct apoptotic stimuli CD95, tumour necrosis factor-alpha (TNFalpha) and UV-irradiation. For the first time in primary hepatocytes, we show that IFNgamma-mediated apoptotic signalling requires the cell surface interaction of CD95 and its ligand, and we demonstrate that IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Fas is constitutively expressed on hepatocytes and its engagement rapidly results in hepatocyte apoptosis in vivo (38). Moreover, the direct apoptotic effects of IFN-γ on murine hepatocytes may require FasL/Fas interactions (39). With these considerations in mind, we hypothesized that liver injury in Tgfb1 −/− mice is Fas dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Fas is constitutively expressed on hepatocytes and its engagement rapidly results in hepatocyte apoptosis in vivo (38). Moreover, the direct apoptotic effects of IFN-γ on murine hepatocytes may require FasL/Fas interactions (39). With these considerations in mind, we hypothesized that liver injury in Tgfb1 −/− mice is Fas dependent.…”
Section: Resultsmentioning
confidence: 99%
“…CBDL has been used as an animal model of chronic liver injury because it duplicates the retention of toxic bile acids during human cholestatic liver disease. The LHBDL model is used to study prolonged liver fibrogenesis independent of liver failure 27. This model of LHBDL allows a comparison of the injured ligated left lobe and the nonligated right lobe.…”
Section: Discussionmentioning
confidence: 99%
“…The c‐Myc oncogene, which is induced during BDL,25 functions as a positive regulator of cell proliferation and growth. Paradoxically, c‐Myc can also result in the sensitization of cells to apoptosis under conditions of hepatocyte injury 27. Max serves as an obligate heterodimerization partner for Myc, allowing it to bind E‐box consensus sequences to activate transcription 11.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several cytokines that are secreted in response to liver damage such as IFNγ, TNFα, IL-2, IL-4 and IL-6 contribute to NK cell activation (Notas et al 2009). Interestingly, NK and NK-T cells are a major source of interferon gamma (IFNγ) which has been shown to cause apoptosis of hepatocytes (Kano et al 1997; McCullough et al 2007). However, the significance of this report has been challenged by a recent study by Masson et al which demonstrated that dimethyl sulfoxide (DMSO, which was used as vehicle for the first study) and not acetaminophen, triggers activation and recruitment of NK cells in liver (Masson et al 2008).…”
Section: Structure and Cellular Components Of The Livermentioning
confidence: 99%